Induction of junB expression, but not c-jun, by granulocyte colony-stimulating factor or macrophage colony-stimulating factor in the proliferative response of human myeloid leukemia cells. - Adachi, K; Saito, H (The Journal of Clinical Investigation, 1992)
The proliferative effects of granulocyte colony-stimulating factor (G-CSF) and macrophage colony-stimulating factor (M-CSF) on human hematopoietic cells have been reported, but the intranuclear mechanism of early signal response to these mitogenic stimuli remains unknown. Using an established human myeloid leukemia cell line (NKM-1) which can grow in serum-free medium in response to G-CSF or M-CSF, we examined expressions of the jun family genes, c-jun, junB, and junD, which are coexpressed by various growth factors in many tissues. In parallel with regrowth from the G0/G1 resting state by addition of recombinant human G-CSF or M-CSF after serum deprivation, NKM-1 cells showed the transient expression of the junB gene with a peak of ninefold above the basal level between 40 and 60 min. In contrast, c-jun expression was not stimulated by these CSFs. JunD expression was constitutively observed at detectable levels. Furthermore, c-fos mRNA was rapidly induced to a peak of 14-fold after CSF stimulation. Transcriptional run-on assays revealed that treatment of serum-starved NKM-1 with 50 ng/ml G-CSF or M-CSF increased the transcription rate of the junB gene and the c-fos gene by 1.8-fold and 2.9-fold, respectively, but did not induce any transcript of the c-jun gene. The results indicate that the expression of the junB and c-fos genes is activated, at least in part, at the transcriptional level in response to these CSFs. These findings suggest that the signal activating c-jun expression might not be involved in the proliferative action of G-CSF and M-CSF but junB may be one of important elements in early response events of the signal transduction system in human CSF-responsive hematopoietic cells. Images